PROBLEMATIKA PEMBELAJARAN DIFFERENSIASI PADA KURIKULUM MERDEKA DI DI SMP MUHAMMADIYAH 2 KARANG TENGAH OKU TIMUR - Amirin, Zainal; Suyadi, Suyadi; Perawironegoro, Djamaluddin; Widodo, Hendro (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Teaching methods are very important in every learning so that students do not get bored while learning. SMP Muhammadiyah 2 Karang Tengah implements an independent curriculum for two years, which is only implemented in class VII and not all. Therefore, the method used must be versatile and stimulate students well. This type of research is qualitative with a field research type. This study uses direct observation, interviews, documentary research and field notes as well as various book and journal references as data collection methods. When implementing an independent learning plan, especially using differentiated learning, most teachers do not yet have an understanding of the planning and implementation of differentiated learning. Teachers still do not know how to manage classes with different types of student characteristics because they have different learning readiness, interests, abilities and styles and learning needs. This certainly requires flexible, versatile, and innovative learning services by paying attention to the characteristics of students so that they can optimally understand the skills developed and learning materials.